2019
DOI: 10.1177/0022185618814580
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy for women migrant workers in Malaysia through an intersectionality lens

Abstract: Analysing labour migration through the lens of intersectionality provides valuable insights into the complex identities of women migrant workers and the multiple discriminations they struggle with. Intersectionality advocates argue that only through adopting such an approach can women’s multiple discriminations be challenged. Drawing on a case study of seven non-governmental organisations and one focus group of women migrant workers in a non-Western context, Malaysia, we explore how advocacy organisations unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Premature dismissals from employment are financially detrimental to both employers and migrant workers. Nevertheless, we found that information and access to family planning are seldom supplied to migrant workers by employers and not provided for by the government [ 20 ]. The state and employers essentially deny that migrant workers are sexually active adults, with the intent of avoiding being seen as promoting promiscuity by raising the topic of SRH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature dismissals from employment are financially detrimental to both employers and migrant workers. Nevertheless, we found that information and access to family planning are seldom supplied to migrant workers by employers and not provided for by the government [ 20 ]. The state and employers essentially deny that migrant workers are sexually active adults, with the intent of avoiding being seen as promoting promiscuity by raising the topic of SRH.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ratification of the Convention on the Elimination of Discrimination against Women (CEDAW) and commitments to the ICPD Programme of Action [ 16 ], Malaysia has not fully recognised the migrant workers’ SRHRs [ 17 , 18 ]. Female migrant workers in Malaysia still face SRHR-related difficulties, mainly through the prohibition of pregnancy during employment [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, we see that the majority of the work focusing on precarious employment in Malaysia is concerned with the plight of migrant workers, especially those working within the palm oil industry or as domestic workers (Pye et al 2012;Kumar et al 2014;Au et al 2019;Miles et al 2019). With regards to the former, Malaysia's palm oil sector is heavily reliant upon roughly 1 million migrant workers, the majority of whom are from neighbouring Indonesia (Pye et al 2012, p. 330).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is estimated that there are currently 300,000-400,000 (ILO, 2013). This may also be attributed to the 'livein' arrangement of most MDWs in Malaysia, who are hidden from view and are denied social status, economic resources, and political voice, making it difficult to uncover their abuse (Carens, 2013;Huling, 2012;Miles et al, 2019). The live-in arrangement blurs the separation between working hours and non-working hours.…”
Section: Malaysiamentioning
confidence: 99%
“…Yet their experiences have largely been invisible in mainstream WL literature. Despite their substantial number globally, MDWs constitute an 'invisible' workforce due to the nature of domestic work and their low-waged, low-skilled status (Miles, Lewis, Teng, & Yasin, 2019). To address this void and inspired by a feminist commitment to promote voices that are not typically included (Thompson, Rickett, & Day, 2018), this paper explores one research question: How do women live-in MDWs talk about their lived experience of the WL interface?…”
Section: Introductionmentioning
confidence: 99%